A prospective study of insulin resistance among infertile women with polycystic ovarian syndrome - Smitha, M.; Jyothi, S.; Acharya, Anand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Insulin plays a key role in producing hyperandronism and suppression of insulin secretion in women with PCOS is associated with decreased cytochrome P450c17α. cytochrome P450c17α is a bifunctional enzyme present in ovary is a key enzyme for androgen synthesis. Various studies have been conducted regarding association of insulin resistance with PCOS in infertile patients but there is no study is available about this in our area. So we have designed this study to evaluate insulin resistance in infertile patients with PCOS in rural Andhra Pradesh. Methods: The study population include 180 untreated patients who attended the infertility clinic in outpatient department of obstetrics with infertility due to different cause that include polycystic ovarian disorder also. They have been selected for this study randomly based on inclusion and exclusion criteria. Results: The mean value of glucose insulin ratio was 5.146+2.611 in group A and 8.62 + 5.55 in group B the P value was 0.004909. The mean of LH/FSH ratio was 1.78+0.423 in group A and 1.02 +0.042 in group B. The P value was <0.00001. The mean of HOMA IR was 8.375+ 2.68 in group A and 3.03+ 1.09 in group B, with P value <0.00001. The mean value of QUICKI was 0.2815+ 0.0002875 in group A and 0.347+0.10 in group B with P value <0.00001. Mean serum DHEAS level was 275.59 + 53.48 in infertile patient with PCOS and 208.48 + 36.11 in infertile patients without PCOS. The p value was 0.00012. Conclusions: Based on present study we would like to conclude that the body mass index was high among infertile women with PCOS and a greater number of women presented with acanthosis. There was decrease insulin sensitivity and increase insulin resistance among infertile women with poly cystic ovarian disease, in rural area of Andhra Pradesh and that is not different from the study of other part of world.